Bibliometric Analysis: Contructivism Approach in Junior High School Geometry Learning in Indonesia (2017-2023) - Ningrum, Sri Adiningsih Utami; Fitriana, Laila (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2024)
Constructivism is a learning theory perspective that strongly influences how mathematics is learned. Since secondary school students are just beginning to recognize and understand abstract thought processes, it is not appropriate to educate them through meaningless memorization, especially in mathematics which is full of abstract symbols. The writing of this article aims to find out the research trends regarding the constructivism approach and to find out the research themes that have the opportunity to be used as research in the future. The method in this research is using bibliometric analysis. Research data obtained through Harzing's Publish or Perish software with Google scholar database, keywords constructivism and junior high school geometry and the result of the maximum number "1000", the article obtained as many as 996 articles with a period of 2017-2023. Then limited to accredited journals sinta 2 obtained 50 articles. The results showed that the publication trend with the research theme of the constructivism approach experienced the highest increase between 2017 - 2020. In addition, the theme of research on the constructivism approach that has the opportunity to be used as research in the future there are four keywords, namely constructivism and Realistic Mathematics Education (RME).